Alan Watts and the re-visioning of psychotherapy. (2nd October 2017) - Sanders, Colin James
ABSTRACT: Alan Watts' seminal text Psychotherapy East and West was authored near Humanistic Psychology's beginnings, also a transformational time for psychotherapy theory and practice. Watts fostered appreciation for Eastern philosophical traditions, particularly in relation to self, identity, and counterculture. In this article, contributions of innovative thinkers cited by Watts, including Gregory Bateson, Erich Fromm, Jay Haley, George Herbert Mead, Rollo May, and Carl Rogers, are highlighted and historically situated toward tracking threads of contemporary influence vis-à-vis social construction, brief therapy, and therapeutic simplicity. The article begins with a brief note on Watts' countercultural positioning.